Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1128/mcb.14.1.170
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of DNA end joining in a mammalian cell nuclear extract: junction formation is accompanied by nucleotide loss, which is limited and uniform but not site specific.

Abstract: Mammalian cells have a marked capacity to repair double-strand breaks in DNA, but the molecular and biochemical mechanisms underlying this process are largely unknown. A previous report has described an activity from mammalian cell nuclei that is capable of multimerizing blunt-ended DNA substrates (R. Fishel, M.K. Derbyshire, S.P. Moore, and C.S.H. Young, Biochimie 73:257-267, 1991). In this report, we show that nuclear extracts from HeLa cells contain activities which preferentially join linear plasmid substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…Extensive analysis of end-joining reactions of plasmid DNA have demonstrated that short sequence homologies at the termini play a role in the repair of extrachromosomal DSBs in vivo (44) and in DNA end joining as tested in cell extracts (35,39). Our data support the relevance of these studies to the repair of chromosomal DSBs.…”
Section: Resultssupporting
confidence: 77%
“…Extensive analysis of end-joining reactions of plasmid DNA have demonstrated that short sequence homologies at the termini play a role in the repair of extrachromosomal DSBs in vivo (44) and in DNA end joining as tested in cell extracts (35,39). Our data support the relevance of these studies to the repair of chromosomal DSBs.…”
Section: Resultssupporting
confidence: 77%
“…NHEJ often involves short sequence homology between the joined ends, and additions or deletions of approximately 25 nucleotides or less at the junctions. 34,36,37 Similar processes have been shown to occur during chromosomal double-strand break (DSB) repair, 27,29,38 which again suggests that extrachromosomal and chromosomal repair are mediated by similar cellular machinery.…”
Section: Introductionmentioning
confidence: 73%
“…Junctional sequence analysis revealed the existence of various different junction types with distinct features which led to the postulation of different pathways of DNA end joining (21,22,25,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms of DNA end joining have been investigated in detail in a variety of eucarytic in vivo (cultured mammalian cells, [13][14][15][16]; Xenopus laevis eggs, 17; yeast, 9,18,19) and in vitro systems (extracts from Xenopus laevis eggs [20][21][22]; nuclear extracts from human cells, [23][24][25][26][27] all of which were shown to be able to join DNA termini containing either blunt ends or short protruding single strands (PSS). Junctional sequence analysis revealed the existence of various different junction types with distinct features which led to the postulation of different pathways of DNA end joining (21,22,25,26,27).…”
Section: Introductionmentioning
confidence: 99%